Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Café Jiwa Siswa Kampung Baru Kota Sorong - Adrianus Manuel Kiabeni; Lili Sarce Joi Sapari; Ade Andriani Renouw (Departement of Mathematics Education, 2023)
This stady aims to determine the effect or service quality on customer satisfactionat the promise soul cafe sorong.the problem in this study is wheter service quality has a satisfaction at the promise soul café in sorong. The type of research used is descriptive whit the surfei method. The research sample is 40 customers and the data collected are primary and secondary data. The analytical model used is simple linear regression ,correlation, coefficient of determination and hypothesis testing using SPSS 25. The results of this study indicate a positive and significant effect or service quality on customer satisfaction at the promise soul cafe in sorong.